Factors driving digital transformation: Technological, organizational, and environmental perspectives from Jordanian banks - Mohammad O. Al-Smadi (Banks and Bank Systems, 2025)
In recent years, the digital transformation of financial institutions has gained the attention of researchers and practitioners all over the world. This study investigates the impact of organizational, environmental, and technological factors on the digital transformation process of Jordanian banks. The approach used in this study is quantitative, and an online questionnaire was forwarded to employees in 15 Jordanian banks. The convenience sampling method was utilized to collect data from 286 participants with a response rate of 35%. Partial least squares structural equation modeling was used for analysis. The results show a significant positive relationship between organizational, environmental, and technological factors and digital transformation, which confirmed the imperative role of organizational, technological, and environmental factors in the digital transition process in Jordanian banks. The results highlight the need for Jordanian banks to develop explicit strategies that involve the integration of new technologies, regulatory frameworks that encourage modern technology adoption, and dealing with different environmental factors. The study thus proposes recommendations for Jordanian banks to achieve maximum benefit from digital transformation and manage the difficulties arising from this transformation in the changing banking sector.